Blockchain technology adoption for carbon trading and energy efficiency: ISO manufacturing firms in Malaysia - Fernando, Yudi; Tseng, Ming-Lang; Wahyuni-TD, Ika Sari; Sroufe, Robert; Mohd-Zailani, Nik Ida Amiera (Taylor and Francis Ltd., 2022)
This study aims to investigate organisational factors of blockchain adoption for carbon trading and energy efficiency. This study develops a new theoretical model based on technology, organisation and environment (TOE), and Diffusion of Innovation (DOI) theories to fill the literature gaps. The underpinning theories are utilised to capture the motivation of manufacturing industry firms to adopt blockchain technology while supporting carbon trading activities. Using survey data, we examine the perception of early adopters of blockchain technology and their relationships to energy efficiency. The results show that attributes such as the contract system, firm size, and compatibility significantly affect energy efficiency. Paradoxically, top management support, competitive pressure, regulatory support, relative advantage, and complexity were not, as prior literature suggests, crucial drivers. Adopting blockchain technology can help a firm improve business transparency, manage energy consumption, and provide a strong business case for firms in this study.